UJI TOKSISITAS EKSTRAK ETANOL BUAH MERAH (Pandanus conoideus Lam) ASAL MANOKWARI PAPUA BARAT DENGAN METODE BRINE SHRIMP LETHALITY TEST - Safriani Rahman; Riyan Wulansari Puspa Seruni (Fakultas Farmasi UMI, 2011)
A research on Toxicity assay of Extract Ethanol Red Fruit (Pandanus conoideus Lam) upon Brine Shrimp Lethality Test which intended to know the toxic effect of Red Fruit and supposed to determine Lc50 of the Red fruit by method Brine Shrimp Lethality Test. The ethanol ekstrak, was made in various concentration 10, 100, 1000 µg/ml. Mean while, for negative control was seawater which made by the same concentration. In each concentration has put in 10 brine shrimp. Each concentration has put 1 drop of yeast extract as source of food. The volume is added to 10 ml, observation is done after 24 hours treatment. Observation result in dead brine shrimp data. From the counted of probit analysis method obtained Lc50 value was that 52,844 ± 25,679 µg/ml. Mean while in negative compare there were not brine shrimp killed. Key words : Pandanus conoideus Lam, Brine Shrimp Lethality Test, Toxicity assay